High-resolution tracking technology reveals distinct patterns in nocturnal crop raiding behaviour of an African elephant (Loxodonta africana) in Amboseli, Kenya - Ryan Wilkie; Iain Douglas-Hamilton (Pachyderm)
Conflict between humans and elephants is a notoriously complex problem requiring a detailed understanding of the underlying patterns and processes in order to develop effective solutions. Advances in radio tracking technologies have enabled researchers to examine in detail the ways in which tracked animals interact with their environments. We analysed the movement patterns of an habitual crop raiding African elephant (Loxodonta Africana) in the Amboseli ecosystem in southern Kenya. We identified three distinct patterns of movement associated with instances of crop raiding; these were (1) opportunistic raiding, (2) purposeful raiding, and (3) incidental raiding. The distinct characteristics of each of these movements serve to demonstrate the differing circumstances under which elephants are brought into contact with agricultural areas in their daily negotiations of the network of human land-use and protected areas. These findings highlight the need to understand patterns of elephant movement and interactions with farmland in order to craft management strategies that are effective in reducing levels of human-elephant conflict and promote tolerance of elephants in rural communities.